The Influence of Labor Environment Settings on Labor Progression - Dewi Sartika Siagian1, Arum Meirani2, Nanik Cahyati3, Lusi Lestari4, Fania5 (Institute of Medico-legal Publications Pvt Ltd, 2020)
The environment in labor can have a great effect on the fears and anxieties experienced by the mother. Anxietycan inhibit cervical dilatation, so that the perception of pain increases. Cortisol is secreted in response totension and anxiety, it affects the progress of cervical dilatation. The increasing concentration of cortisolduring pregnancy and continue to rise until labor. Anxiety is usually associated with increased pain duringlabor and modification of labor pain can be done through psychological and physiological mechanisms. Oneway to modify psychological labor pain is by setting the delivery environment. The purpose of this studywas to analyze the effect of the setting of the labor environment on the progress of labor.The results showed the average delivery progress (cm/hour) in the treatment group 1.38 (0.43) and thecontrol group 1.23 (0.52), obtained p = 0.058, this indicates there was no difference in labor progress in bothstudy groups. Based on the statistical test results of the effect of the setting of the delivery environment onthe progress of labor, the p value = 0.015 shows that there is an influence of the delivery environment settingon the progress of labor and the RR value of 3.67 (IK = 1.14-11.84), which means that the mother givesbirth in a Independent Midwifery Practice (IMP) who did not manage the delivery environment had a risk ofhaving a cervical opening < 1 cm/hour by 3.67 times compared to mothers giving birth at the IMP who didthe setting of the delivery environment.The conclusion of this research is that there is a positive influence of the delivery environment to the progressof labor.